2012
DOI: 10.1111/j.1476-5381.2011.01630.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT receptors as novel targets for optimizing pigmentary responses in dorsal skin melanophores of frog, Hoplobatrachus tigerinus

Abstract: BACKGROUND AND PURPOSEBiochemical identification of 5-HT has revealed similar projection patterns across vertebrates. In CNS, 5-HT regulates major physiological functions but its peripheral functions are still emerging. The pharmacology of 5-HT is mediated by a diverse range of receptors that trigger different responses. Interestingly, 5-HT receptors have been detected in pigment cells indicating their role in skin pigmentation. Hence, we investigated the role of this monoaminergic system in amphibian pigment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…The pieces were kept in 10 mL of amphibian Ringer saline (ARS) containing 111 mM of sodium chloride, 2 mM potassium chloride, 1 mM calcium chloride, and 2 mM sodium hydroxide in 100 mL of double distilled water at pH 7.4 in small Petri dishes, and they were equilibrated in saline medium for 15–20 min with frequent stirring. The dorsal skin pieces of the B. melanostictus , containing about 30–50 melanophores in the control ARS, had the tendency of dispersion within a period of 30–60 min; hence, they were brought to the intermediate state of neither aggregation nor dispersion by using a very low concentration of adrenaline (2 × 10 −8 g/mL) as per the modified standard methods of Ali et al [ 11 ], Ryan et al [ 12 ], and Ali et al [ 13 ]. This facilitated the accurate measurement of the dispersal responses of the melanophores induced by the berberine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pieces were kept in 10 mL of amphibian Ringer saline (ARS) containing 111 mM of sodium chloride, 2 mM potassium chloride, 1 mM calcium chloride, and 2 mM sodium hydroxide in 100 mL of double distilled water at pH 7.4 in small Petri dishes, and they were equilibrated in saline medium for 15–20 min with frequent stirring. The dorsal skin pieces of the B. melanostictus , containing about 30–50 melanophores in the control ARS, had the tendency of dispersion within a period of 30–60 min; hence, they were brought to the intermediate state of neither aggregation nor dispersion by using a very low concentration of adrenaline (2 × 10 −8 g/mL) as per the modified standard methods of Ali et al [ 11 ], Ryan et al [ 12 ], and Ali et al [ 13 ]. This facilitated the accurate measurement of the dispersal responses of the melanophores induced by the berberine.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of various adrenergic, cholinergic, histaminergic, and serotonergic drugs [ 5 6 7 8 9 10 11 12 13 ] have been studied on lower-vertebrate melanocytes, since they are a disguised type of smooth-muscle cell, and the mechanism of skin darkening is analogous to contraction and relaxation of the smooth-muscle cells of higher animals [ 14 15 ]. The pharmacological aspects of the intracellular displacement of melanosomes in vertebrate melanophores or melanocytes have rarely been studied at ultrastructural level, keeping in view the therapeutic approach toward melanin dysfunctions, like vitiligo/leukoderma, hypopigmentation, etc .…”
Section: Introductionmentioning
confidence: 99%
“…5-HT, a monoamine, could stimulate smooth muscle contraction and regulate ion selection and permeability of epithelial cells, processes which play a key role in water exchange of frog's skin [3,14]. Some studies demonstrated that pigment cells of amphibians contain 5-HT receptor, and indicated that 5-HT had physiological effects on skin color changes [15]. In our present study, the positive reaction of 5-HT is the strongest among these six GI hormones, in particular, we found the higher immunoreactivity in the skin glands, what suggests that 5-HT may be also important in self-defense and regulation of the secretion of glands.…”
Section: Discussionmentioning
confidence: 99%
“…Receptor systems participate in a very coordinated manner in mediation of responses of color change [21]. Cellular receptors of adrenergic, cholinergic, histaminergic, and serotonergic nature have been found to regulate pigmentation via melanin displacement in various animal melanocyte models [22][23][24].…”
Section: Morpho-anatomical Aspects Of Mammalian Melanocytesmentioning
confidence: 99%